Contrasting patterns in biomass allocation, root morphology and mycorrhizal symbiosis for phosphorus acquisition among 20 chickpea genotypes with different amounts of rhizosheath carboxylates. (29th April 2020) - Wen, Zhihui; Pang, Jiayin; Tueux, Guillaume; Liu, Yifei; Shen, Jianbo; Ryan, Megan H.; Lambers, Hans; Siddique, Kadambot H. M.
Abstract: Adjustments in root biomass allocation, root morphology, carboxylate exudation and mycorrhizal symbiosis are well‐known strategies for plants to cope with phosphorus (P) deficiency. Large genotypic variation in these functional traits has been demonstrated within numerous species. Yet, whether these functional traits are coordinated differently among genotypes of a species to enhance P acquisition remains unknown. We characterized 11 root functional traits associated with P acquisition in 20 chickpea genotypes with contrasting amounts of rhizosheath carboxylates, grown in a glasshouse with severely limiting insoluble (10 mg/kg FePO4 ), moderately limiting soluble (10 mg/kg KH2 PO4 ) and adequate (50 mg/kg KH2 PO4 ) P supply. Substantial variation was found among genotypes in root functional traits associated with P acquisition. Genotypes with a large amount of carboxylates (HRC) had thinner roots, and a lower root mass fraction and root mass density (RMD), but higher specific root length (SRL) and colonization by arbuscular mycorrhizal fungi (AMF) than genotypes with a small amount of rhizosheath carboxylates. In response to soil P availability, chickpea genotypes showed large plasticity in root biomass allocation, rhizosheath pH, carboxylate amount and colonization by AMF, but a limited response in most root morphological traits (i.e. mean root diameter, RMD and SRL). Shoot P content was strongly correlated with different root functional traits in the three P treatments. Our findings suggest a range of predictable relationships between root functional traits among chickpea genotypes; those with HRC tended to have relatively thinner roots with lower cost of root construction, while allocating more resources to carboxylate exudation and colonization by AMF. The shift in the relationships between shoot P content and root functional traits indicates that root traits and/or trait combinations in chickpea vary in a manner that enhances P acquisition under specific soil P conditions (i.e. P sources/levels). Such knowledge provides valuable information for chickpea genotype breeding and our understanding of evolution of traits with improved root/rhizosphere functioning. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article